A Noble‐Metal‐Free System for Photocatalytic Hydrogen Production from Water. Issue 47 (10th October 2013) - Mejía, Esteban; Luo, Shu‐Ping; Karnahl, Michael; Friedrich, Aleksej; Tschierlei, Stefanie; Surkus, Annette‐Enrica; Junge, Henrik; Gladiali, Serafino; Lochbrunner, Stefan; Beller, Matthias
Abstract A series of heteroleptic copper(I) complexes with bidentate <![CDATA[$\widehat{PP}$]]> <inline-graphic xlink:href="ark:/27927/pgg4t7pjg52" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and <![CDATA[$\widehat{NN}$]]> <inline-graphic xlink:href="ark:/27927/pgg4t7pjg3z" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> chelate ligands was prepared and successfully applied as photosensitizers in the light‐driven production of hydrogen, by using [Fe3(CO)12] as a water‐reduction catalyst (WRC). These systems efficiently reduces protons from water/THF/triethylamine mixtures, in which the amine serves as a sacrificial electron donor (SR). Turnover numbers (for H) up to 1330 were obtained with these fully noble‐metal‐free systems. The new complexes were electrochemically and photophysically characterized. They exhibited a correlation between the lifetimes of the MLCT excited state and their efficiency as photosensitizers in proton‐reduction systems. Within these experiments, considerably long excited‐state lifetimes of up to 54 μs were observed. Quenching studies with the SR, in the presence and absence of the WRC, showed that intramolecular deactivation was more efficient in the former case, thus suggesting the predominance of an oxidative quenching pathway.